Algebraic Expressions

The cube of binomial
The binomial expansion algorithm
The difference of two squares, multiplying
The difference of two squares, factoring
The difference of two cubes
The sum of two cubes
Cube of a binomial
To the cube of the first term add, three times the product of the square of the first term and the last term, three times the product of the first term and the square of the last term, and the cube of the last term.
 Examples: a)  (a - b)3 = (a - b)2 · (a - b) = (a2 - 2ab + b2) · (a - b) = = a3 - 2a2b + ab2 - a2b + 2ab2 - b3 = a3 - 3a2b + 3ab2 - b3, b)  (x - 2)3 = x3 + 3 · x2 · (-2) + 3 · x · (-2)2  + (-2)3 = x3  - 6x2 + 12x - 8, c)  (2x + y)3 = (2x)3 + 3 · (2x)2 · y + 3 · (2x) · y2  + y3 = 8x3 + 12x2y + 6xy2  + y3.
The binomial expansion algorithm - the binomial theorem
The binomial expansion of any positive integral power of a binomial, which represents a polynomial with n + 1 terms, or written in the form of the sum formula  is called the binomial theorem.
The binomial coefficients can also be obtained by using Pascal's triangle.
 The triangular array of integers, with 1 at the apex, in which each number is the sum of the two numbers above it in the preceding row, as is shown in the initial segment in the diagram, is called Pascal's triangle. So, for example the last row of the triangle contains the sequence of the coefficients of a binomial of the 5th power.
 n 1 1 1 1 2 1 2 1 3 1 3 3 1 4 1 4 6 4 1 5 1 5 10 10 5 1 - 1 - - - - - 1
 Example: The difference of two squares, multiplying
 (a - b) · (a + b) = a2 - ab + ab - b2 = a2 - b2
 Examples: a)  (x - 2y) · (x + 2y)  = x2 - 2xy + 2xy - 4y2  = x2 - 4y2 b)  (3a + 1) · (3a - 1)  = 9a2 + 3a - 3a - 1  = 9a2 - 1
The difference of two squares, factoring
 a2 - b2 = (a - b) · (a + b)
 Examples: a)  1 - 16y2  = 12 - (4y)2  = (1 - 4y) · (1 + 4y) b)  1/9a4 - 0.0001  = (1/3a2)2 - (0.01)2  = (1/3a2 - 0.01) · (1/3a2 + 0.01)
The difference of two cubes
 a3 - b3 = (a - b) · (a2 + ab + b2)
 Examples: a)  8x3 - 125  = (2x)3 - 53  = (2x - 5) · (4x2 + 10x + 25) b)  1 - 27a3  = 13 - (3a)3  = (1 - 3a) · (1 + 3a + 9a2)
The sum of two cubes
 a3 + b3 = (a + b) · (a2 - ab + b2)
 Examples: a)  8 + x3  = 23 + x3  = (2 + x) · (4 - 2x + x2) b)  64a3 + 0.001  = (4a)3 + 0.13  = (4a + 0.1) · (16a2 - 0.4a + 0.01)   Functions contents A 